Efeitos do tratamento com captopril e losartan em ratos Wistar e ratos espontaneamente hipertensos submetidos a hipertensão arterial pulmonar com monocrotalina - Waichert Júnior, Élio (2011)
The pulmonary arterial hypertension (PAH) is a disease that begins with increased of pulmonary arterial resistance. After installation, several changes on the cardiovascular, respiratory and autonomic system are observed. Despite the studies available in the literature, the development of this disease in experimental models of hypertension remains to be studied, as well as the therapeutic effects of the renin angiotensin system in the reversal of this disease. The aims of the present study were to evaluate cardiovascular, autonomic and respiratory effects produced by monocrotaline (MCT)-induced PAH in Wistar and SHR animals and the therapeutic effects of the chronic treatment with captopril and losartan in reversing PAH. For this, we used Wistar (150-180 g) and SHR (150-180 g) divided into the following groups: Wistar control treated with saline or MCT (WIS-CON-SAL and WIS-CON-MCT, respectively), SHR control treated with saline or MCT (SHR-CON-SAL and SHRCON-MCT, respectively), Wistar treated with captopril + saline or MCT (WIS-CPTSAL and WIS-MCT-CPT, respectively), SHR treated with captopril + saline or MCT (SHR-CPT-SAL and SHR-MCT-CPT, respectively), Wistar treated with losartan + saline or MCT (WIS-LOS-SAL and WIS-LOS-MCT, respectively) and SHR treated with losartan + saline or MCT (SHR-LOS-SAL and SHR-LOS-MCT, respectively). In the animals treated with MCT, a single dose was injected (60 mg/Kg, SC) and control animals were submitted to a saline injection in the same volume (~0,8 mL). At the end of the 3ª week, when MCT-treated animals presented HAP, it was made the treatment with captopril (100 mg/Kg/mL ) or losartan (30 mg/Kg/mL) in drinking water for 2 weeks and daily volume of 30 mL. After these treatments, cardiovascular, respiratory, gasometrical recordings and pulmonary histology were performed. Results showed a significant increase in the pulmonary index in the control animals MCT-treated (Wistar and SHR) when compared to respective control group. The ventricular pressures (SPmax, IDP and FDP) were also significantly increased in the MCT´s group, as well as systolic and diastolic blood pressure, heart rate, pressure pulse and arterial pressure lability. The treatment with captopril normalized all of parameters studied, however, losartan showed inefficient to normalize these parameters. The morphometric analysis showed an increase in the thickness of the media layer of the distal branches pulmonary arterial and a decreasing of the lumen in the MCT-treated groups. The treatment with both captopril and losartan normalized these parameters but the losartan-treated group had been less efficient than captopril, once these treatments showed significant differences each other. In relation to autonomic evaluation, the MCT-treated animals showed an increasing of the cardiac sympathetic tonus and a reduction in the parasympathetic tonus. Once more, the treatment with captopril normalized these parameters, while losartan treatment was inefficient to normalize. In relation respiratory parameters, we observed increases in the tidal volume, respiratory rate, pulmonary ventilation and alveolar ventilation in the control animals MCT-treated. Only captopril normalized these parameters. The gasometrical evaluation showed that control groups MCTtreated showed reduction in partial tension of O2 (hypoxia), increasing in partial tension of CO2 (hypercapnia), fall in percentage of hemoglobin saturation (% Hb), increasing in bicarbonate (HCO3 - ) and acidosis. Captopril normalized all of these gasometrical parameters, while the same was not observed to losartan in SHR animals HAP-induced. Our results showed that MCT-induced to the HAP picture in Wistar and SHR animals, as well as important cardiovascular, autonomic, respiratory, gasometrical and pulmonary morphological changes. The treatments with captopril and losartan were able to reverse HAP in Wistar and SHR animals, however, captopril was more effective in normalizing these parameters when compared to losartan. These results suggest that the use of blockers of the renin angiotensin system may be a therapeutic option for the treatment of PAH.